International Capital Flows Within the European Monetary Union: Increasing Economic Divergence Between the Centre and the Periphery - Sergio Rossi (Intervention. Zeitschrift fuer Ökonomie / Journal of Economics, 2007)
This paper aims at investigating some neglected consequences of free capital mobility in the Euro area. The approach we use in this work is based on the bookkeeping nature of money, which shows that capital - in the form of bank deposits - is mobile within a currency area but actually immobile between different monetary spaces. Within the Euro area both short- and long-term investments are directed into those economies where the return on investment is highest, a magnitude that is positively correlated with the rate of real growth. If so, then economic divergence might increase between member countries of the European Monetary Union (EMU), giving rise thereby to a higher rate of unemployment in those member countries that suffer from net capital outflows, to the benefit of some other countries in the same area.
Keywords: E31; E63; F21; F36; 330; capital mobility; economic divergence; monetary policy; monetary union